2004
DOI: 10.1590/s1516-35982004000900012
|View full text |Cite
|
Sign up to set email alerts
|

Uréia para vacas leiteiras no pós-parto: desempenhos produtivo e reprodutivo

Abstract: RESUMO -Quinze vacas mestiças (Holandês-Zebu) com peso médio de 511,8 kg foram distribuídas ao acaso em quatro tratamentos, sendo quatro animais nos tratamentos 1, 2 e 4 e três animais no tratamento 3. Os tratamentos foram constituídos de dietas à base de volumoso (silagem de milho) e concentrado (60:40), fornecidas individualmente e à vontade, e definidos como: T 1 =0,0; T 2 =0,7; T 3 =1,4 e T 4 =2,1% de uréia, correspondendo às concentrações de 2,08; 4,01; 5,76 e 8,07% de proteína bruta na forma de compostos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
4
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
2
4
1
Order By: Relevance
“…The PUN level in the cows receiving sugarcane with 12 g UAs/kg (14.31 mg/dL) was similar to that observed by Rangel et al (2008), in cows receiving sugarcane with the same UAs level, without effect on intake. The PUN value in this study was, however, smaller than values observed in studies in which intake reduced as UAs were increased (from 19.90 to 23.08 mg/dL) (Silva et al 2001a,b;Oliveira et al, 2001;Oliveira et al, 2004). The lower PUN value observed in the present study in relation to those of Silva et al (2001a,b), Melo et al (2003) and Oliveira et al (2004) is possibly related to the nature of the dietary carbohydrates present in the sugarcane, which are mostly soluble in neutral detergent, especially those rich in sugars, of higher rumen degradation rate in relation to the amylaceous fractions, and the ones insoluble in neutral detergent, which are typical in silages of corn and sorghum (Lanzas et al, 2007).…”
Section: Resultscontrasting
confidence: 79%
See 4 more Smart Citations
“…The PUN level in the cows receiving sugarcane with 12 g UAs/kg (14.31 mg/dL) was similar to that observed by Rangel et al (2008), in cows receiving sugarcane with the same UAs level, without effect on intake. The PUN value in this study was, however, smaller than values observed in studies in which intake reduced as UAs were increased (from 19.90 to 23.08 mg/dL) (Silva et al 2001a,b;Oliveira et al, 2001;Oliveira et al, 2004). The lower PUN value observed in the present study in relation to those of Silva et al (2001a,b), Melo et al (2003) and Oliveira et al (2004) is possibly related to the nature of the dietary carbohydrates present in the sugarcane, which are mostly soluble in neutral detergent, especially those rich in sugars, of higher rumen degradation rate in relation to the amylaceous fractions, and the ones insoluble in neutral detergent, which are typical in silages of corn and sorghum (Lanzas et al, 2007).…”
Section: Resultscontrasting
confidence: 79%
“…The PUN value in this study was, however, smaller than values observed in studies in which intake reduced as UAs were increased (from 19.90 to 23.08 mg/dL) (Silva et al 2001a,b;Oliveira et al, 2001;Oliveira et al, 2004). The lower PUN value observed in the present study in relation to those of Silva et al (2001a,b), Melo et al (2003) and Oliveira et al (2004) is possibly related to the nature of the dietary carbohydrates present in the sugarcane, which are mostly soluble in neutral detergent, especially those rich in sugars, of higher rumen degradation rate in relation to the amylaceous fractions, and the ones insoluble in neutral detergent, which are typical in silages of corn and sorghum (Lanzas et al, 2007). A higher rumen degradation rate of the fraction of sugars propitiates greater synchrony with the rate of rumen ammonia availability through urea, allowing for lower accumulation of rumen ammonia (Nocek & Russell, 1988).…”
Section: Resultscontrasting
confidence: 79%
See 3 more Smart Citations